Soil fertility and fertilizers - Tisdale, Samuel (MacMillan, 1975)
Contents:soil fertility past and present; soil and fertilizer potassium magnesium, calcium, and sodium; soil fertility evaluation; economics of lime and fertilizer use; fertilizer and efficent use of water.